2017
DOI: 10.1002/2016wr019832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐concentration rhamnolipid biosurfactant on Pseudomonas aeruginosa transport in natural porous media

Abstract: Enhanced transport of microbes in subsurface is a focus in bioaugmentation applications for remediation of groundwater. In this study, the effect of low‐concentration monorhamnolipid biosurfactant on transport of Pseudomonas aeruginosa ATCC 9027 in natural porous media (silica sand and a sandy soil) with or without hexadecane as the nonaqueous phase liquids (NAPLs) was studied with miscible‐displacement experiments using artificial groundwater as the background solution. Transport of two types of cells was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 70 publications
3
19
0
1
Order By: Relevance
“…The background solutions used in the all experiments were artificial ground water (AGW). It consists of (per liter): 0.006 g NaCl, 0.012 g CaSO 4 , 0.012 g NaHCO 3 , 0.002 g KNO 3 , and 0.035 g MgSO 4 ·7H 2 O (pH 6.8) (Liu, Zhong, et al, ). The CMCs of the SDBS and TX‐100 in AGW are 204 and 195 mg/L, respectively (Zhong, Zhang, et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The background solutions used in the all experiments were artificial ground water (AGW). It consists of (per liter): 0.006 g NaCl, 0.012 g CaSO 4 , 0.012 g NaHCO 3 , 0.002 g KNO 3 , and 0.035 g MgSO 4 ·7H 2 O (pH 6.8) (Liu, Zhong, et al, ). The CMCs of the SDBS and TX‐100 in AGW are 204 and 195 mg/L, respectively (Zhong, Zhang, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for the cell transport experiments were similar to that described by Liu, Zhong, et al (). In brief, the columns were preequilibrated with at least 30 pore volumes (PVs) of bacteria‐free AGW solutions before each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The successful bioremediation (bioaugmentation in particular) depends on effective transport of injected bacteria over considerable distances and adequate distribution of the injected bacteria throughout the contaminated area (Liu, Zhong, et al, ). However, the soil has a great adsorption capacity and straining potential for bacterial cells, which may significantly reduce the concentration of suspended bacterial cells as they transport (Zhong, Liu, et al, ).…”
Section: Remediation Of Organic Contaminationmentioning
confidence: 99%
“…For example, it was reported that low concentration of rhamnolipid significantly attenuated hydrophobic interactions between P. aeruginosa cells and glass beads, and hence reduced cell adsorption and enhanced cell transport (Zhong, Jiang, et al, ; Zhong, Liu, et al, ). The effect of low‐concentration mono‐rhamnolipid on transport of P. aeruginosa cells in natural porous media (silica sand and a sandy soil) with or without hexadecane as the nonaqueous phase liquid (NAPL) was further investigated in the study of Liu, Zhong, et al (), wherein it was observed that transport of cells in natural porous media was enhanced by rhamnolipid through decreasing bacterial CSH, and the relative enhancement in the presence of NAPL was greater than that in the absence of NAPL.…”
Section: Remediation Of Organic Contaminationmentioning
confidence: 99%
See 1 more Smart Citation